Challenges to the Multi-Functional Uses and Multifarious Benefits of Urban Green Spaces: Basis of Urban Biodiversity Planning and Management in the City of Manila, Philippines - Leonora Gonzales; Dina Magnaye (Environmental Science and Sustainable Development, 2016)
Urbanization is a global phenomenon which is projected by the United Nations to grow annually at 65 million between 2000 and 2030 in developing countries. As an archipelagic nation, the Philippines is considered as a highly urbanized nation where over three-fourths of its population is estimated to reside in urban areas, posting a proportion of one person residing in rural area for every three in urban area. The National Capital Region (NCR), the core region of the counry, registers a 100% urbanization level and where the most densely populated areas converged. It generally exhibits an urban population growth rate that exceeds the national growth rate. Manila, the capital city of the Philippines, is the second largest and the world’s most densely populated city given its small land area and huge human population. The concentration of people in this city and the urbanization processes are foreseen to create environmental stress leading to potential biodiversity losses coupled with other urban environmental occurrences such as flooding, air pollution, sea level rise, earthquake, subsidence, traffic congestion, water pollution, among others. These natural and man-made hazards pose challenge to the multi-functional uses and various benefits of urban green spaces (UGS). UGS play a significant role in enhancing the quality and resiliency of the environment as well as in improving the health and general well being of city dwellers. It is in this context that the challenges and opportunities of UGS are examined. The paper attempts to identify and determine the factors that influence UGS as basis for urban biodiversity planning and management.